Mewujudkan Keadilan Realitas dalam Putusan Penguasaan Anak Melalui Pendekatan Interkoneksi Sistem - Kurniawan, M. Beni (Jurnal Penelitian Hukum De Jure, 2025)
Child custody disputes are one of the absolute authorities of religious courts. In 2023 there were 1526 (one thousand five hundred and twenty six) cases of child custody disputes examined and decided by all religious courts in Indonesia. The problem is that even though the court has given a decision that is legally binding on the child custody holder, the reality is that many of the religious court decisions are not heeded by the losing party due to several factors, including hiding the child, taking the child away, or inciting the child, which has an impact on the non-executionability of the child custody decision. Departing from this problem, this paper formulates the problem of how legal regulations in Indonesia regulate child custody and how the application of the interconnection system in carrying out child custody decisions. This paper applies normative juridical research methods by examining related legal documents as the main source of reference. the author's findings that for the realization of reality justice in child custody decisions, the Court can adopt an inter-connection system by involving relevant to prevent non-executable decisions.